பொதுக்கலைக்களஞ்சியம் : தொகுதி - 9 - (:unkn) unknown (Tamil Valarchi Kazhagam, 1956)
This book imparts general encyclopedic knowledge about various subjects.
Tamil Encyclopedia Kalaikkalanjiyam ( General) : Volume-9
Keywords: Tamil; Encyclopedia; Tamil